Bauhaus in Wien? Möbeldesign, Innenraumgestaltung und Architektur der Wiener Ateliergemeinschaft von Friedl Dicker und Franz Singer - Hövelmann, Katharina (2021)
The furniture, interior designs and buildings by Friedl Dicker and Franz Singer were exceptional in Vienna in the 1920s and 1930s. In this study, based on extensive source research in Amsterdam, Berlin, London, Weimar and Vienna, the work of the studio community is analysed for the first time in the context of the Bauhaus and the Viennese architectural landscape. The volume, which is equipped with numerous previously unpublished illustrations, closes a gap in research on Viennese architectural history and the Bauhaus.